Moral Space Through Professional Solidarity - Hanson, Stephen (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2026)
Creating moral space involves actions and omissions. An important omission of solidarity is to refuse to hold or attend professional conferences in countries and American states where laws and social approbation make it uncomfortable, unwise, or dangerous for certain members of the professional community to attend. Markowitz’s Impermissible Sacrifice Principle, which she used to critique abortion policies, is employed to show why it is wrong to hold a professional conference in such a state and why solidarity requires the support of all moral persons. While this article describes the importance of this principle now in terms of LGBTQ+ persons, it may also apply soon or even now with regard to persons of colour, women, and/or visiting non-American citizens. It is also shown why solidarity against impermissible sacrifices is a better way to ground decisions about locating or attending conferences than a teleological argument about boycotts to change policy.